2022
DOI: 10.3389/fnut.2022.811826
|View full text |Cite
|
Sign up to set email alerts
|

Psoas Muscle Index Can Be Used to Predict Long-Term Mortality in Young Male Patients With Acute-on-Chronic Liver Failure

Abstract: ObjectiveThe use of psoas muscle index (PMI) in acute-on-chronic liver failure (ACLF) has not been reported, and the aim of this study was to evaluate the predictive value of PMI for the prognosis of patients with ACLF.MethodsIn this study, male ACLF patients who underwent abdominal CT between 2015 and 2019 in our center were included to analyze the association between PMI and 1-year mortality in male ACLF patients, and subgroup analyses were performed according to age stratification (≤ 40 and >40 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Interestingly, the results of this study detected the predictive value of SMI for the clinical outcome of ACLF in young men up to 40 in age, but not in older men. Similar to this work, our earlier study failed to observe the correlation between PMI and mortality in men older than 40 years with ACLF ( 20 ). The possible reason is that, in older individuals, aging has a greater effect on reducing skeletal muscle mass than liver failure.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, the results of this study detected the predictive value of SMI for the clinical outcome of ACLF in young men up to 40 in age, but not in older men. Similar to this work, our earlier study failed to observe the correlation between PMI and mortality in men older than 40 years with ACLF ( 20 ). The possible reason is that, in older individuals, aging has a greater effect on reducing skeletal muscle mass than liver failure.…”
Section: Discussionsupporting
confidence: 88%
“…Our previous study revealed that muscle loss is particularly pronounced after the age of 40 ( 13 ). Besides, we found that L3-PMI was independently associated with 1-year mortality in male ACLF patients younger than 40 years, which was not observed in male ACLF patients beyond 40 years ( 20 ). Thus, we assessed SMI levels in the age ≤ 40 years and > 40 years groups, respectively.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…A new PMI-based criterion for skeletal muscle mass has been established using data from healthy young Asian adults, which defines a cut-off value for sarcopenia in Asian populations [ 18 ]. In addition to evaluating sarcopenia, PMI can predict long-term mortality in young men with chronic or acute liver failure [ 19 ]. Several other studies have shown that PMI can be applied to Marfan syndrome and the prognosis of different tumor surgeries [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have attempted to use the total psoas area or the psoas muscle index at L3/L4 [50]. However, there is a lack of evidence supporting a significant correlation between the psoas muscle and total body muscle and its association with the prognosis of sarcopenia in patients with cirrhosis [28,51]. Meanwhile, there is significant correlation in muscle measurements between T12/L4 and L3 [36,52,53], so it is possible that muscle mass measurement at other vertebral segments apart from L3 could also accurately diagnose sarcopenia and predict survival in patients with cirrhosis and sarcopenia, though further studies are needed before this measurement can be widely recommended.…”
Section: Muscle Mass/quantitymentioning
confidence: 99%